Cardiac Computed Tomography: Application in Valvular Heart Disease - Patel, Kush P.; Vandermolen, Sebastian; Herrey, Anna S.; Cheasty, Emma; Menezes, Leon; Moon, James C.; Pugliese, Francesca; Treibel, Thomas A. (Frontiers in Cardiovascular Medicine, 2022)
The incidence and prevalence of valvular heart disease (VHD) is increasing and has been described as the next cardiac epidemic. Advances in imaging and therapeutics have revolutionized how we assess and treat patients with VHD. Although echocardiography continues to be the first-line imaging modality to assess the severity and the effects of VHD, advances in cardiac computed tomography (CT) now provide novel insights into VHD. Transcatheter valvular interventions rely heavily on CT guidance for procedural planning, predicting and detecting complications, and monitoring prosthesis. This review focuses on the current role and future prospects of CT in the assessment of aortic and mitral valves for transcatheter interventions, prosthetic valve complications such as thrombosis and endocarditis, and assessment of the myocardium.